Transfer of Fibres onto Knife Blades in Stabbing Events: Distribution and Determination of the Stabbing Sequence - Michael Schnegg; Line Gueissaz; Jessica Rodriguez; Sabine Hess; Genevieve Massonnet (Wolters Kluwer Medknow Publications, 2015)
Knives are among the weapons most frequently involved in criminal cases. They represent the most encountered category of weapons in Swiss homicide cases (completed and attempted homicides considered) and are also frequently employed in assault cases, notably bodily injuries. Whenever a knife is involved in a stabbing event, DNA and fingerprints may be sought. When garments are damaged, fibres can also be investigated. Fibres from the victim's garments might transfer onto the blade of the knife used in the assault and can thus provide useful information to determine whether a particular weapon could have be used to stab the victim. This study simulates vertical stabbings into garments with the use of a special holding device. Different types of knives and blades straight or serrated were used as weapons. Two garments presenting different shedding capacities and garment structures were also considered for the simulations. The distribution of fibres transferred onto the blade (number and position) was recorded for each simulation performed. Sequences of stabbings into the two garments were also carried out to assess whether the order of the stabs could be determined. Several parameters were considered, notably the distribution of fibres transferred onto the blade. The transfer of fibres inside the stab damage ballistic soap was used in this study and on the area near the second damage was also investigated. This study provides new insight into the interpretation of fibres transferred onto knives after a single stab or a sequence of stabbings and into determining the stabbing sequence. Finally, the study brings some guidelines for the search and recovery of fibres on the crime scene and on the blades of knives.